Determinants of MSME Interest in Binjai City Using E-Payment as a Payment Method - Mutiara, Mutiara; Muliyani, Muliyani (SEIKO : Journal of Management & Business, 2024)
This research was conducted on several MSMEs in Binjai City. The purpose of this research is to determine whether or not there is interest in of course MSMEs in Binjai City in using E-Payment services as a payment method by assessing perceived ease of use, perceived benefits and perceived risks. This research uses associative quantitative methods. This research is associative quantitative research (relationship or influence). Associative research is "research that aims to determine the relationship between two or more variables". The form of relationship in this research is a causal relationship, namely a cause and effect relationship caused by the independent variable. Type of p data collection carried out in this research in the form of collecting questionnaires or questionnaires at the research location, namely u MSMEs in Binjai City and only MSMEs that have used digital payment methods or E-Payment.